2020
DOI: 10.1097/bsd.0000000000001064
|View full text |Cite
|
Sign up to set email alerts
|

Depression Identified on the Mental Component Score of the Short Form-12 Affects Health Related Quality of Life After Lumbar Decompression Surgery

Abstract: Study Design: This was a retrospective comparative study. Objective: The goal of this study was to further elucidate the relationship between preoperative depression and patient-reported outcome measurements (PROMs) following lumbar decompression surgery. Summary of Background Data: The impact of preoperative depression on PROMs after lumbar decompression surgery is not well established. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Previous research in patients undergoing ACDF has demonstrated an association between preoperative depressive symptoms and worse clinical outcomes postoperatively, although those with depressive symptoms still achieved significant improvement following surgery 13–16. Similar results have also been reported postoperatively in patients undergoing lumbar decompression with or without fusion 17–21…”
supporting
confidence: 54%
See 4 more Smart Citations
“…Previous research in patients undergoing ACDF has demonstrated an association between preoperative depressive symptoms and worse clinical outcomes postoperatively, although those with depressive symptoms still achieved significant improvement following surgery 13–16. Similar results have also been reported postoperatively in patients undergoing lumbar decompression with or without fusion 17–21…”
supporting
confidence: 54%
“…Our findings suggest that patients with depression will have meaningful one-year postoperative patient-reported improvements following surgery, and they should not be excluded from surgical intervention based on their mental health history, aligning with previous studies in ACDF and lumbar surgery. 15,17,21 An important finding from our study is the high rate of revision surgery in patients with a past medical history of depression and/or anxiety. Although our cohort of nondepression/anxiety patients had revision rates below 1%, which was comparable to the 1.1% pooled revision rate found in a meta-analysis of 31 PCDF studies, our overall revision rate was 4.1%.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations